2008
DOI: 10.2334/josnusd.50.53
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of periodontitis in oral fluids

Abstract: Matrix metalloproteinases (MMPs), the key enzymes responsible for matrix degradation, are derived from polymorphonuclear leukocytes during the early stages of periodontitis. The present study determined the levels of GCF matrix metalloproteinase-2 (MMP-2) and metalloproteinase-9 (MMP-9) and salivary MMP-8 in patients with gingivitis and periodontitis and in healthy controls. Levels of crevicular MMP-2, MMP-9 and salivary MMP-8 were determined by ELISA in subjects with healthy gingiva (n = 15), gingivitis (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
118
3
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(146 citation statements)
references
References 17 publications
16
118
3
1
Order By: Relevance
“…Periodontal microbes and host-derived proteases could degrade host periodontal proteins and proteins involved in the inflammatory and immune reactions into peptides and amino acids that the microorganisms can absorb and used as nutritional resources (Sandholm, 1986;Eley and Cox, 2003). Studies have shown elevated levels of peptides and amino acids in periodontal population (Rai et al, 2008;Barnes et al, 2011). The increased peptides and amino acids would supply as a richer energy pool for the expansion of some specific organisms relying on oligopeptides as carbon and energy sources (Takahashi and Sato, 2002) that ultimately influences the microbial and functional structure.…”
Section: Discussionmentioning
confidence: 99%
“…Periodontal microbes and host-derived proteases could degrade host periodontal proteins and proteins involved in the inflammatory and immune reactions into peptides and amino acids that the microorganisms can absorb and used as nutritional resources (Sandholm, 1986;Eley and Cox, 2003). Studies have shown elevated levels of peptides and amino acids in periodontal population (Rai et al, 2008;Barnes et al, 2011). The increased peptides and amino acids would supply as a richer energy pool for the expansion of some specific organisms relying on oligopeptides as carbon and energy sources (Takahashi and Sato, 2002) that ultimately influences the microbial and functional structure.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, saliva can be collected under conditions in which blood collection would be difficult or inadvisable. Technological advances have improved experimental approaches, thereby eliminating limitations on using saliva as a diagnostic tool in monitoring health or disease status (23)(24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…The residual bacteria may activate dentinal MMPs, contributing to the breakdown of demineralized collagen matrices and weakened dentin structure. MMPs, as collagenase and gelatinase have been found in gingival crevicular fluid and saliva (55)(56)(57)(58). Given the various sources of collagenase, a non-specific collagenase inhibitor with high inhibition, physico-chemical characteristic to adhere to inherently moistened dentin, and with substantivity is desired.…”
Section: Interaction Between Bacteria and Host-derived Mmpsmentioning
confidence: 99%